The present and future disease burden of hepatitis C virus infections with today's treatment paradigm – volume 3. (December 2015) - Sibley, A.; Han, K. H.; Abourached, A.; Lesmana, L. A.; Makara, M.; Jafri, W.; Salupere, R.; Assiri, A. M.; Goldis, A.; Abaalkhail, F.; Abbas, Z.; Abdou, A.; et al.
Summary: The total number, morbidity and mortality attributed to viraemic hepatitis C virus (HCV) infections change over time making it difficult to compare reported estimates from different years. Models were developed for 15 countries to quantify and characterize the viraemic population and forecast the changes in the infected population and the corresponding disease burden from 2014 to 2030. With the exception of Iceland, Iran, Latvia and Pakistan, the total number of viraemic HCV infections is expected to decline from 2014 to 2030, but the associated morbidity and mortality are expected to increase in all countries except for Japan and South Korea. In the latter two countries, mortality due to an ageing population will drive down prevalence, morbidity and mortality. On the other hand, both countries have already experienced a rapid increase in HCV‐related mortality and morbidity. HCV‐related morbidity and mortality are projected to increase between 2014 and 2030 in all other countries as result of an ageing HCV‐infected population. Thus, although the total number of HCV countries is expected to decline in most countries studied, the associated disease burden is expected to increase. The current treatment paradigm is inadequate if large reductions in HCV‐related morbidity and mortality are to be achieved.